2014
DOI: 10.1002/cpp.1896
|View full text |Cite
|
Sign up to set email alerts
|

Early Maladaptive Schemas: A Comparison Between Bipolar Disorder and Major Depressive Disorder

Abstract: Early maladaptive schemas are relevant psychological dimensions to consider in remitted phases of major mood disorders. Findings from the current study suggest that early maladaptive schemas are more prevalent in adults with bipolar disorder compared to adults with major depressive disorder when measured during remission. Interventions targeting early maladaptive schemas may be valuable in treatment of bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…17,24 Patients with bipolar disorder differ from patients with major depressive disorder (MDD) in terms of score in some EMS domains. 25 However, more studies are needed to determine the cognitive risk factors for chronic depression. 10,12 The five EMS domains are categorised through robust psychometric methods and represent focused and comprehensive enduring cognitive patterns.…”
Section: Resultsmentioning
confidence: 99%
“…17,24 Patients with bipolar disorder differ from patients with major depressive disorder (MDD) in terms of score in some EMS domains. 25 However, more studies are needed to determine the cognitive risk factors for chronic depression. 10,12 The five EMS domains are categorised through robust psychometric methods and represent focused and comprehensive enduring cognitive patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Young et al (2003) have operationalized 18 different EMSs, which can be measured by the Young Schema Questionnaire (YSQ) (Young, 2005). Previous research indicates that BD patients generally have more severe EMSs than control subjects and major depressive disorder patients (Hawke and Provencher, 2012a;Mehmet et al, 2011;Nilsson et al, 2015). In BD patients, higher EMS scores have furthermore been associated with functional impairments (Nilsson, 2012).…”
mentioning
confidence: 97%
“…These findings demonstrated greater specificity of several maladaptive schemas with respect to BD, that is, grandiosity , approval‐seeking and insufficient self‐control (e.g. Khosravani, Sharifi Bastan, Mohammadzadeh, Amirinezhad, & Samimi Ardestani, 2019; Nilsson, Nielsen Straarup, & Halvorsen, 2015; Özdin et al, 2018). Interestingly, one study (Hawke & Provencher, 2012) also suggested that individuals with BD were likely to endorse emotion inhibition and abandonment less strongly than a mixed group of unipolar depression and anxiety disorders.…”
Section: Resultsmentioning
confidence: 95%
“…Between‐group comparisons with other diagnostic groups suggested that some of these maladaptive schemas might be relatively specific to BD. For example, there were convergent findings that individuals with BD scored higher on grandiosity and approval‐seeking than individuals with unipolar depression (Hawke & Provencher, 2012; Nilsson, Nielsen Straarup, & Halvorsen, 2015; Özdin et al, 2018). In addition, grandiosity and insufficient self‐control were the only two schemas that were elevated in individuals with BD compared with people with obsessive–compulsive disorder and those with schizophrenia (Khosravani, Sharifi Bastan, Mohammadzadeh, Amirinezhad, & Samimi Ardestani, 2019).…”
Section: Resultsmentioning
confidence: 99%